Women, Peace, and Security in Professional Military Education - Perkins, Dana, 1965-; Mackenzie, Lauren, 1976- (Book collections on Project MUSE., 2022)
"The Women, Peace, and Security (WPS) Agenda is a global framework and policy tool that guides national actions addressing gender inequalities and the drivers of conflict and its impact on women and girls. By fostering structural and institutional change, the WPS agenda aims to 1) prevent conflict and all forms of violence against women and girls and 2) ensure the inclusion and participation of women in peace and security decision-making processes to incorporate their specific needs in relief and recovery situations. This volume gathers together student papers from the Joint Women, Peace, and Security Academic Forum's 2021 WPS in PME Writing Award program, a best-of selection of informative and empowering work that intersects with Department of Defense equities supporting global WPS principles. Student participants in the Joint WPS Academic Forum hail from prestigious DOD academic institutions, and this monograph shows how the strategic leaders of tomorrow embrace WPS today, offering a strong indication of how WPS principles will be implemented over time and how they will influence the paradigm of peace and security and our approaches to conflict prevention and resolution"--